2016
DOI: 10.1177/0892705715604680
|View full text |Cite
|
Sign up to set email alerts
|

Analytical investigation of high-velocity impact on hybrid unidirectional/woven composite panels

Abstract: In addition to fiber properties, the fabric structure plays an important role in determining ballistic performance of composite body armor textile. Textile structures used in ballistic protection are woven fabrics, unidirectional fabric structures and nonwoven fabrics. In this paper an analytical model based on wave propagation and energy balance between the projectile and the target is developed to analyze hybrid fabric panels for ballistic protection. The hybrid panel consists of two types of structure, wove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…High strength and toughness fabrics such as Kevlar, Twaron and Spectra and composites made from these fabrics are usually used as soft body armor [3,4]. During the last decade numerous researches have been carried out on the high velocity impact on high strength fabric structures [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…High strength and toughness fabrics such as Kevlar, Twaron and Spectra and composites made from these fabrics are usually used as soft body armor [3,4]. During the last decade numerous researches have been carried out on the high velocity impact on high strength fabric structures [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…(Chen et al., 2014) found that the front layers of fabric are more likely to be broken in shear, and the rear layers of fabric tend to fail in tension. Shanazari et al. (2017) developed an analytical model based on wave propagation and energy balance between the projectile and the target to analyze hybrid fabric panels for ballistic protection.…”
Section: Introductionmentioning
confidence: 99%
“…The studies found deal with ballistic performance of thick hybrid composite panels for body armors [39,40] or low velocity impact on UD composite laminate positioned between two ply of 5HS fabric carbon to protect it [41].…”
Section: Introductionmentioning
confidence: 99%